Content analysis of booking.com reviews on hotel in Penang - Salman, Nur Fadhilah; Md Sawari, Siti Salwa (2019)
The accessibility to internet and online payment system has boost the use of online platform to booked accommodations. Reviews in online booking platform has become one of the factors that influence accommodations selections of future tourist. Majority academic papers that study on tourist preference on accommodation are using quantitative research. Hence, the purpose of this study is to analyse the reviews in Booking.com using qualitative methods to reveal the tourist experience and preference of accommodations. This study is focused on Eastern & Oriental Hotel where content analysis are made on a total of 435 reviews in Booking.co websites within year 2019. This study also used word cloud to visualise the data. The data are coded to major themes which are locations, facilities, service, value, food and living environment. The findings of this study identified that locations are the attributes of accommodations that matter the most among tourist. This study also found that most tourist are satisfied with the hotel as the most suggested hotel in Booking.com. The contribution of this study will give benefits to the hotel investors by having vision into customers’ preference, the investment made will swiftly returned with increasing profit.